2014
DOI: 10.1177/0961000614530752
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of job satisfaction among Croatian librarians as support to library human resource management

Abstract: In the ICT-dominated world, libraries are facing major challenges in an attempt to fulfil their functions. If libraries are to respond adequately to rapid and complex changes, they need highly skilled and motivated employees. As people are an organization’s greatest asset, human resource management in libraries should be given proper attention. Different questions related to job satisfaction are definitely crucial for efficient human resource management. This paper presents the results of research focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Based on the analysis and findings and conclusions outlined in this study, it proposes suggestions since the satisfaction of visitors in the Library Office of South Sumatra Province is already high, so that library staff must maintain and increase visitor satisfaction both in terms of interpersonal communication of library staff and from other aspects (13) (14). Library visitors are expected to establish contact with library staff, whether asking questions when experiencing difficulties or providing input to library staff (15,16). It is hoped that further researchers can develop this research by using interpersonal communication theory and other visitor satisfaction theories that are the topic of discussion to be studied (17,18).…”
Section: Discussionmentioning
confidence: 96%
“…Based on the analysis and findings and conclusions outlined in this study, it proposes suggestions since the satisfaction of visitors in the Library Office of South Sumatra Province is already high, so that library staff must maintain and increase visitor satisfaction both in terms of interpersonal communication of library staff and from other aspects (13) (14). Library visitors are expected to establish contact with library staff, whether asking questions when experiencing difficulties or providing input to library staff (15,16). It is hoped that further researchers can develop this research by using interpersonal communication theory and other visitor satisfaction theories that are the topic of discussion to be studied (17,18).…”
Section: Discussionmentioning
confidence: 96%
“…Major reasons for Kuwaiti professional librarians' job dissatisfaction were salary, benefits, working conditions and prospects for promotion. Similarly, a study by Dukic and Dukic (2014) found that Croatian librarians positively evaluated their jobs, but were less satisfied with their social status, salary, working conditions and options for further training.…”
Section: Status and Prestige Of The Lis Professionmentioning
confidence: 99%